Gender Differences in Social Adjustment and Interpersonal Support among Undergraduate Students - Kaur, Rajinder; Sharma, Seema (International Journal of Bio-resource and Stress Management, 2022)
The present study was conducted during 2019 in Guru Nanak Dev University, Amritsar (GNDU); Punjab Agricultural University, Ludhiana (PAU) and Punjabi University, Patiala (PUP), Punjab, India to investigate the gender differences and relationship between social adjustment and interpersonal support among university students of Punjab. The sample consisted of 480 university students randomly selected from three purposively selected government universities of Punjab state i.e. Guru Nanak Dev University, Amritsar; Punjab Agricultural University, Ludhiana and Punjabi University, Patiala, India. An equal number of students distributed across both the gender were randomly selected from each university. Social Adjustment and Interpersonal Support Evaluation Scales were used for the study. The social adjustment of the university students was measured by using the Social Adjustment Scale and Interpersonal Support Evaluation scale was used to measure the peer support available to university students. Data was analyzed using t-test and Karl-Pearson’s coefficient of correlation. The results of the study revealed that male students had displayed significantly better social adjustment and interpersonal support than their female counterparts. Furthermore, correlation analysis emphasized that interpersonal support had positive relationship with social adjustment among male students whereas in case of female students, interpersonal support was found to have non-significant positive relationship with social adjustment. Because female students less likely to express their problems or emotions with their age mates as well as less involved in social activities as compared to male students. Therefore, Interpersonal support played a major role in the social adjustment of the students at university level.